2021
DOI: 10.3390/ph14090864
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ezrin/Radixin/Moesin in the Surface Localization of Programmed Cell Death Ligand-1 in Human Colon Adenocarcinoma LS180 Cells

Abstract: Programmed cell death ligand-1 (PD-L1), an immune checkpoint protein highly expressed on the cell surface in various cancer cell types, binds to programmed cell death-1 (PD-1), leading to T-cell dysfunction and tumor survival. Despite clinical successes of PD-1/PD-L1 blockade therapies, patients with colorectal cancer (CRC) receive little benefit because most cases respond poorly. Because high PD-L1 expression is associated with immune evasion and poor prognosis in CRC patients, identifying potential modulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 72 publications
(95 reference statements)
3
22
0
Order By: Relevance
“…Our present immunoprecipitation analysis demonstrated that not only moesin but also ezrin and radixin physiologically interacted with PD-L1 and the triple complex of PD-L1, ERM, and actin cytoskeleton. This is in agreement with our recent publication that all three ERM proteins interact with PD-L1 as determined by co-immunoprecipitation assays in human colorectal cancer cell line [57]. Collectively, the present and previous findings raise the possibility that ERM function as crosslinkers to regulate the plasma membrane localization of PD-L1 via post-translational modifications in HeLa cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our present immunoprecipitation analysis demonstrated that not only moesin but also ezrin and radixin physiologically interacted with PD-L1 and the triple complex of PD-L1, ERM, and actin cytoskeleton. This is in agreement with our recent publication that all three ERM proteins interact with PD-L1 as determined by co-immunoprecipitation assays in human colorectal cancer cell line [57]. Collectively, the present and previous findings raise the possibility that ERM function as crosslinkers to regulate the plasma membrane localization of PD-L1 via post-translational modifications in HeLa cells.…”
Section: Discussionsupporting
confidence: 93%
“…Meng et al have also reported that cell-surface PD-L1 levels are decreased by treatment with moesin siRNA without any impact on its mRNA expression levels, resulting in T-cell activation in in vitro cell culture model, although the effect of gene silencing of ezrin and radixin has not yet been determined [40]. In contrast, our recent study demonstrated that gene silencing of ezrin and radixin equally decreased the cell-surface PD-L1 levels but not its mRNA expression levels [57]. Given the fact that ERM proteins involved in the plasma membrane localization of P-gp, a typical partner protein for ERM, vary according to the types of cancer, organ, and animal species [33,[59][60][61][62][63], this discrepancy among the present and previous results may be attributed, at least in part, to the different expression profiles of ERM in cancer cell types.…”
Section: Discussionmentioning
confidence: 62%
“…We recently reported that ezrin functions as a scaffold protein for PD-L1, which leads to the cell surface localisation of PD-L1 in human uterine cervical adenocarcinoma HeLa cells and human choriocarcinoma JEG-3 cells, both of which have the highest expression level of ezrin among ERM protein based on the database analysis utilizing DepMap and/or our experimental data [29,30]. Furthermore, we have found that in human colon adenocarcinoma LS180 cells, ezrin and radixin contributed equally to the cell surface localisation of PD-L1 via physiological interaction and colocalisation with PD-L1, despite extremely low expression level of radixin in LS180 cells [31]. By contrast, another group has shown that moesin interacts with and stabilises PD-L1 in the cell surface membrane by preventing the proteasomal degradation of PD-L1 in human breast cancer adenocarcinoma, MDA-MB-231, though the influence of ezrin and radixin gene suppression remains to be determined [47].…”
Section: Discussionmentioning
confidence: 61%
“…Accumulating evidence suggests that radixin principally regulates the surface plasma membrane localisation of numerous drug transporters including multidrug resistance protein 2, presumably because radixin is dominantly expressed in the hepatic tissues and cells among ERM proteins [48][49][50][51][52][53]. Therefore, radixin may primarily contribute to the cell surface localisation of PD-L1 in KP-2 cells as a predominant ERM protein, as is the case with ezrin in HeLa, JEG-3, and LS180 cells we have recently reported [29][30][31]. This issue has yet to be unravelled and should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation